Comunicación de valores intangibles de marca en empresas medianas y grandes de la ciudad de Manizales - Colombia (Dimensión Empresarial, 2022)
This article analyzes the way in which three Colombian companies build their identity, based on the communication of intangible brand values. The theoretical context is constructed through the postulates of identity and brand image, the importance of stakeholders, and especially the postulates of researchers who have determined the way in which intangible values ​​build brand. The methodology consists of in-depth semi-structured interviews with 9 professionals from large and medium-sized companies in the city of Manizales - Colombia (professionals in the branding area of ​​companies) and 3 interviews with experts (design professionals, with profiles related to branding). Both the results and the conclusions allow us to understand the importance of building a good identity through intangible values, as a means to create a correct image and corporate reputation. In addition, to discover what are the intangible values ​​that companies are using to have a better connection with their stakeholders.
Keywords: Identity; brand; stakeholders; intangible values